Control for Wind Power Generation Based on Inverse System Theory - Jiyong Zhang; Guohai Liu (Institute of Advanced Engineering and Science, 2013)
Traditional Double-fed Wind Generation systems are based on the vector control method, and it is dependent on motor parameters. The performance of the control system will be affected with the parameters changing,. This paper proposes a new control method based on inverse system and variable structure sliding mode(VSS) theories, through the inverse system theory, the structure of its state’s equation, obtaining the structure of the inverse system, the establishment of Wind Power Generation closed-loop control system is established. The VSS controller, designed with exponential reaching law, can improve the dynamic performance in normal operation range effectively. When the system operates with variable speed constant frequency (VSCF) and the phase voltage drops, the simulations show that the control system can control the DC link voltage steabily, maintain unity power factor, achieve the decoupling of the active and reactive power. And experiments show that the control method used in VSCF wind power system is feasible. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3534